Higher expected returns for investors in the energy sector in Europe using an ESG strategy - Wanday, Julia; Ajour El Zein, Samer (Frontiers in Environmental Science, 2022)
The energy sector is transforming as new regulations are set in place to take into account the environmental and social factors as well as corporate governance initiatives which can be integrated within organisations. Companies are pushing towards having better environmental, social and governance (ESG) scores as it impacts shareholders, investors, employees, customers amongst many others. The methodology used in this paper is quantitative and includes an analysis of the financial performance of publicly listed companies using return on equity, return on assets, return on sales, return on investment and also used the SARIMA (seasonal autoregressive integrated moving average) model to forecast revenues for the companies included in the research. The aim of this study is to investigate the impact of ESG activities within companies and how it affects investor returns. Considering regional and sectoral effects an observation of a positive relationship between ESG and investor returns is identified.